2014
DOI: 10.1093/abbs/gmu090
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNA expression profile: a novel potential predictor for chronic nervous lesions

Abstract: The mechanisms of chronic neuropathic pain are not clear. Serum microRNAs (miRNAs) might show a special feature for chronic nervous lesions. However, little is known about the changes in circulating miRNAs for the neuropathic pain. Therefore, changes in the circulating miRNAs expression profile for the neuropathic pain were investigated. Serum was collected from rats before and after spinal nerve ligation (SNL) surgery, and a microarray analysis was performed to determine the changes in miRNA expression profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 52 publications
(52 reference statements)
3
19
1
Order By: Relevance
“…12 Serum miR-221 was decreased and moderate negatively correlated with plasma hs-CRP in acute ischemic stroke patients 17 ; miR-221 in the serum of rats after spinal nerve ligation surgery was decreased. 18 Thus, our findings further supported that serum miR-221 may be a potential predictor for disease. In addition, serum miR-221 was positive correlated with UPDRS-III and UPDRS-V scores, although miR-221 was downregulated in serum of most PD patients.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…12 Serum miR-221 was decreased and moderate negatively correlated with plasma hs-CRP in acute ischemic stroke patients 17 ; miR-221 in the serum of rats after spinal nerve ligation surgery was decreased. 18 Thus, our findings further supported that serum miR-221 may be a potential predictor for disease. In addition, serum miR-221 was positive correlated with UPDRS-III and UPDRS-V scores, although miR-221 was downregulated in serum of most PD patients.…”
Section: Discussionsupporting
confidence: 76%
“…In addition, upregulated miR‐195 and downregulated miR‐185, miR‐15b, miR‐221, and miR‐181a can precisely distinguish PD patients from health individuals and may be used as a potential serum‐based biomarker for the diagnosis of PD . Serum miR‐221 was decreased and moderate negatively correlated with plasma hs‐CRP in acute ischemic stroke patients; miR‐221 in the serum of rats after spinal nerve ligation surgery was decreased . Thus, our findings further supported that serum miR‐221 may be a potential predictor for disease.…”
Section: Discussionsupporting
confidence: 76%
“…MiR-133b has been regarded as an important predictor to diagnose and characterize several diseases [17-19]. Recently, a study utilizing bioinformatics data indicated that six circulating miRs, including miR-133b, were most predictive of allergic status, and miR-133b showed decreased plasma level in AR patients [19].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, accumulating evidences suggest that miR-133b may be a novel potential predictor for inflammation. A previous study indicated that the changes of miR-133b expression might involve in the regulation of neuropathic pain, which were correlated with the expression of inflammatory cytokines [17]. Downregulation of miR-133b could be observed in the muscle of patients with inflammatory myopathy [18].…”
Section: Introductionmentioning
confidence: 99%
“…IL-1β, a proinflammatory cytokine, is elevated in patients with neuropathic pain (105). IL-6 is upregulated in human and rat neuropathic nerves (105, 107), and in CSF of human CPRS (106) (complex regional pain syndrome) as well as in serum of nerve-injured rats (108);, gene knockout of IL-6 attenuates allodynia in the SNL mouse model (109). Monocyte chemoattractant protein-1 (MCP-1), a biomarker for human CRPS, is also upregulated in rats (108, 110).…”
Section: Human Chronic Pain and Dynorphinmentioning
confidence: 99%